2014
DOI: 10.1007/s00330-014-3472-7
|View full text |Cite
|
Sign up to set email alerts
|

Internal structures of the globus pallidus in patients with Parkinson’s disease: evaluation with quantitative susceptibility mapping (QSM)

Abstract: The QSM value in GPl increases gradually with age, which allows for the identification of GPm in elderly PD subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 27 publications
5
40
1
Order By: Relevance
“…On the other hand, the lack of a significant age-related difference in the GP with QSM in the present study is consistent with previous post-mortem evidence (Hallgren and Sourander, 1958), and confirmed in vivo (Li et al, 2014), that iron deposition in the GP increases rapidly from birth until the second decade of life but thereafter plateaus. One study, however, reported age-related differences in the GPe-but not GPi-with QSM (Ide et al, 2015). Overall, the differential GP behaviours in the present study are reflected in the existing literature, indeed a meta-analysis of past studies using various MR techniques to estimate iron content concluded that the GP showed the weakest and most inconsistent age-related differences compared to other basal ganglia structures.…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, the lack of a significant age-related difference in the GP with QSM in the present study is consistent with previous post-mortem evidence (Hallgren and Sourander, 1958), and confirmed in vivo (Li et al, 2014), that iron deposition in the GP increases rapidly from birth until the second decade of life but thereafter plateaus. One study, however, reported age-related differences in the GPe-but not GPi-with QSM (Ide et al, 2015). Overall, the differential GP behaviours in the present study are reflected in the existing literature, indeed a meta-analysis of past studies using various MR techniques to estimate iron content concluded that the GP showed the weakest and most inconsistent age-related differences compared to other basal ganglia structures.…”
Section: Discussionsupporting
confidence: 62%
“…Our previous QSM study with normal subjects mentioned differences in the iron deposition with age between the lateral and medial globus pallidus; the QSM value in the lateral globus pallidus significantly increased gradually with age, whereas that in the medial globus pallidus did not increase [25]. Our current results demonstrated that both SLE groups showed significantly higher QSM and R2* values than the controls for the lateral globus pallidus, but not for the medial globus pallidus.…”
Section: Discussioncontrasting
confidence: 67%
“…As the degree of susceptibility to ferritin is much stronger in the brains of individuals free of haemorrhage and aggregates of other metals than in other tissues, QSM can be used to quantify the brain iron distribution [24]. Ide et al reported, by using QSM, the susceptibility differences between medial and lateral globus pallidus related to age separately [25]. Clinical data obtained from MS patients suggest that QSM is more sensitive than R2* mapping for detecting changes in MS brains [12].…”
Section: Introductionmentioning
confidence: 97%
“…With regard to the detection of calcification, several studies suggest that QSM may be superior to conventional SWI in the identification of subtle calcifications and in differentiating microcalcifications from hemosiderin, at the same time also allowing for a quantification [19, 46]. As a consequence, there is a multitude of future clinical applications for QSM, such as in the diagnosis and longitudinal evaluation of quantitative changes in neurodegenerative diseases [47], multiple sclerosis [48] or the prognosis of neoplasms such as glioblastomas [46]. …”
Section: Discussionmentioning
confidence: 99%